Comportamiento de los Parámetros reproductivos de un Hato lechero de raza Holstein Friesian, criado de forma intensiva durante el periodo 2014, Pacasmayo - La Libertad - Aguilar Zavaleta, Luis Angel (2018)
ABSTRACT The study carried out in the present work is to determine the behavior of the reproductive parameters - year 2014 for dairy farming of the Holstein Friesian breed in a stable of the province of Pacasmayo that belongs to the Peruvian coast. Animals of different ages were taken into account. young, and cows, were analyzed by taking into account the seasons of the year, management in the barn and their nutrition. The reproductive indexes were determined: age at the first service (EPS), age at first calving (EPP), interval - first service (IPPS), calving interval - conception (IPC) or open days, interval between calving (IEP), number of services by conception (NSC), global conception rate (GCT) and pregnancy rate (TP); according to the study carried out, EPS was 14.4 ± 1.0 months, the PPA was 24.4 ± 2.5 months, IPPS was 120 ± 64 days, the IPC was 180 ± 99 days, the IEP was 15.8 ± 3.6 months, the NSC in heifers was 1.5 and in cows 4.0 services per pregnancy, TCPS in heifers was 34.2%, in cows 23.3%, TCG in heifers 30.4, in cows 22.7, and TP in cows was 11.0%.